2008
DOI: 10.1007/s10336-008-0354-2
|View full text |Cite
|
Sign up to set email alerts
|

Moult strategies of Cory’s Shearwaters Calonectris diomedea borealis: the influence of colony location, sex and individual breeding status

Abstract: The replacement of old feathers is essential for birds, but it is also an energy-demanding task. As moult usually does not coincide with other stressful events in its annual cycle, such as reproduction and migration, the bird can optimise its use of time and energy allocated to different activities. There are very few studies comparing the moult strategies of populations with similar breeding calendars but occurring in areas of different habitat quality. Cory's Shearwaters Calonectris diomedea have a partial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 33 publications
(69 reference statements)
2
70
1
Order By: Relevance
“…Indeed, the phenomenon could result from sex-related differences in the timing and/or extent of moult (Weimerskirch 1991;Svensson and Nilsson 1997;Hemborg and Merrilä 1998). However, such differences are generally observed in species showing a marked sexual dimorphism and tend to be absent or negligible in species with a reduced one (Alonso et al 2009). In addition, temperate species tend to concentrate their moult in a few weeks (Ginn and Melville 1983), whereas moult in tropical species can spread over several months and overlap with breeding (Wyndham 1986;Tidemann and Woinarski 1994), possibly as an adaptive strategy for non-migratory individuals living in habitats with sufficient and constant food supply to allow yearround breeding (Foster 1974;Barta et al 2006;EcheverryGalvis and Hau 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the phenomenon could result from sex-related differences in the timing and/or extent of moult (Weimerskirch 1991;Svensson and Nilsson 1997;Hemborg and Merrilä 1998). However, such differences are generally observed in species showing a marked sexual dimorphism and tend to be absent or negligible in species with a reduced one (Alonso et al 2009). In addition, temperate species tend to concentrate their moult in a few weeks (Ginn and Melville 1983), whereas moult in tropical species can spread over several months and overlap with breeding (Wyndham 1986;Tidemann and Woinarski 1994), possibly as an adaptive strategy for non-migratory individuals living in habitats with sufficient and constant food supply to allow yearround breeding (Foster 1974;Barta et al 2006;EcheverryGalvis and Hau 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that, during the late nesting season, Cory's Shearwaters that experience a breeding failure use the discretionary time and energy at their disposal to begin the annual molt of flight feathers sooner than successful breeders (Alonso et al 2009). Hence, once freed from reproduction individuals are able to allocate more resources to selfmaintenance, which may release them from constraints that more stringently limit the migration strategies of the birds that raise a chick to fledging.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, (primary) moultbreeding overlap does occur in petrels that are longdistance migrants (e.g. Alonso et al 2009), as birds have the option of starting moult while still breeding, and then suspending it until after they reach the winter quarters (Ramos et al 2009). This allows them to migrate without the need to allocate energy and nutrients to feather synthesis, as well as avoid costs related to gaps in the wing plumage at a time when efficiency during long-distance flight is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…Black-browed albatrosses from the Falklands generally enjoy a higher breeding success and a lower incidence of breeding deferral by experienced breeders (skipping breeding in 1 year) than their counterparts from South Georgia (Arnold et al 2006;Nevoux et al 2010;Catry et al 2011). If this indicates a more benign environment, presumably with greater food availability, we could predict a higher moultbreeding overlap in the Falklands, as in these conditions individual birds would be in a better position to simultaneously invest in offspring and self-maintenance (Alonso et al 2009). Furthermore, as birds do not usually moult during migration, sedentary albatrosses from the Falklands may have more time to carry out a more extensive moult than those from South Georgia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation